2018
DOI: 10.1111/ped.13710
|View full text |Cite
|
Sign up to set email alerts
|

Family characteristics and children's knowledge of cardiovascular risk factors

Abstract: Background Cardiovascular disease has the highest mortality rate than any other disease globally. Some major risk factors seem to be established in the early stages of life, suggesting preventive strategies as a major means to reduce cardiovascular mortality. The aim of the present study was to investigate the role of socioeconomic status and family characteristics on children's knowledge and perceptions concerning cardiovascular disease risk factors. Methods A cross‐sectional survey was conducted among 1,728 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It has also been observed that children living with both parents have greater awareness of cardiovascular risk factors and more correct eating habits than their counterparts whose parents are separated 42,43 …”
Section: Early Oxidative Stress and Maternal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that children living with both parents have greater awareness of cardiovascular risk factors and more correct eating habits than their counterparts whose parents are separated 42,43 …”
Section: Early Oxidative Stress and Maternal Healthmentioning
confidence: 99%
“…40,41 It has also been observed that children living with both parents have greater awareness of cardiovascular risk factors and more correct eating habits than their counterparts whose parents are separated. 42,43 Over recent years, the number of grandparents who take care of their grandchildren has been on an upward trend. Coexistence with grandparents is beneficial for children and adolescents' health, most of all when they are primary caregivers.…”
Section: Preterm Birth Metabolic Alterationsmentioning
confidence: 99%
“…Several other studies have revealed that poor HL is associated with stigma and poor self-esteem (12,13). Family structure as a role model in determining children's personality, lifestyle, and social behaviors has long been studied (14)(15)(16)(17)(18)(19). In a systematic review, three dominant areas in the parental influence of children's eating habits were revealed: (a) active guidance/education, (b) psychosocial mediators, and (c) moderating influence of general parenting styles (15).…”
Section: Introductionmentioning
confidence: 99%